The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1748-1716.2011.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of respiratory pattern on lung mechanics and interstitial proteoglycans in spontaneously breathing anaesthetized healthy rats

Abstract: This study suggests that the breathing pattern induced by the different anaesthetic regimen may damage the pulmonary interstitium even during spontaneous breathing at physiological tidal volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
12
0
1
Order By: Relevance
“…Higher respiratory rate in spontaneously breathing rats led to increased activation of lung tissue metalloproteinases and reduced integrity of the extracellular matrix in the lung [31]. Wang et al reported an association between metalloproteinase 9 and upregulation of iNOS via nuclear factor-κβ [32].…”
Section: Discussionmentioning
confidence: 99%
“…Higher respiratory rate in spontaneously breathing rats led to increased activation of lung tissue metalloproteinases and reduced integrity of the extracellular matrix in the lung [31]. Wang et al reported an association between metalloproteinase 9 and upregulation of iNOS via nuclear factor-κβ [32].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the duration of the experiment was quite short (3 hours), so that different effects might be observed with longer periods of mechanical ventilation. Lastly, the type of sedation during spontaneous breathing and paralyzing agents during mechanical ventilation may affect lung inflammation [14,15]. …”
mentioning
confidence: 99%
“…On the other hand, Al Jamal et al showed that extremely high VT (30 ml/kg) and high respiratory rate (90 breaths/minute) induce the expression of versican (CS-PG), basement membrane HS-proteoglycan (HS-PG), and biglycan in lung tissue [16]. Moriondo et al also observed CS and HS fragmentation at high VT [6] and showed that the fluid overload associated with high-VT mechanical ventilation worsened GAG fragmentation, mainly in the ventral lung regions [13].…”
Section: The Ecm and Ventilator-induced Lung Injurymentioning
confidence: 93%
“…Recently, breathing patterns induced by different anesthetic regimens were shown to trigger disorganization and/or remodeling of the ECM. An anesthetic mixture of pentobarbital/urethane led to fragmentation of heparan sulfate (HS) and chondroitin sulfate (CS) [13]. In addition, at low VT, application of positive end-expiratory pressure (PEEP) seems to be protective [14], mainly in the ventral lung regions [15], reducing disruption of GAGs and PGs [14,15].…”
Section: The Ecm and Ventilator-induced Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation